Authority control and its role in uniting old arabic authors entries at the Central Library of the University of Baghdad and the Al-Mustansiriya: A Comparative Study - صالح, منى هادي; فرج, خالدة جمال (Journal of Economics and Administrative Sciences, 2017)
The research aims to identify the positives formulation entrances authors depending on the setting retaining the names of the authors of Arab veterans and cons of setting the entrances to Arab authors ancient depending on the nickname by desktop diligence without reference to a setting retaining the potential to benefit other libraries disciple of retaining existing in sober university libraries. Use the survey method and adopted a questionnaire distributed to the research sample consisting of employees working in the libraries in question and the total number of forms that have been distributed (50) form .tousel search phrase conclusions from them .1-The lack of authority control depends on it to find a formula used for the name of the author makes it difficult to know the names of the entrances to the authors, because the search for the formula used for the author's name in the books of references is difficult and takes time and effort.2-some of the names that did not exist in a number of references, as shown through research in a sample Central Library of the University of Baghdad. Some of the names does not match the others, we find the name varies depending on the source, leading to confusion and confusion work and this is what has been observed in the sample taken in the search.The most important proposals that have been developed in the research were as follows :-1-need to do exactly retaining libraries for each of the central libraries because of its role in uniting the authors entrance. The need to consolidate retaining control of libraries to prevent the dispersion of the entrances to the names of the authors.-3availability of retaining control on the Internet in order to benefit from other libraries in the creation of its own tuning retaining.